2020
DOI: 10.3390/agriculture10120600
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pulsed Arc Discharge Exposure to Impede Expansion of the Invasive Vine Pueraria montana

Abstract: The invasive kudzu vine Pueraria montana var. lobata is an agricultural nuisance that disturbs the field cultivation of crop plants. We developed a simple electrostatic method of suppressing the invasive growth of kudzu vines as an alternative to the use of herbicides for weed control. Exposure of the vine apex to a high-voltage arc discharge was the focal point of the study. To achieve this, we constructed a ladder-shaped apparatus by arranging several parallel copper rods at specific intervals in an insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Our supplementary experiment also indicated that the houseflies that approximately 50% of their body water by dehydration received no arcing due to reduced conductance, i.e., an increase in resistivity in the water-depleted houseflies due to the arc-discharge exposure (Figure S1B). Matsuda et al [24] reported that continuous pulsed arc-discharge exposure to the growing stem tip of the kudzu plant (Pueraria montana) raised the temperature of the exposed region, implying that an increase in temperature caused the vaporization of body water. Additionally, we simultaneously transferred two houseflies onto the G-MN and examined the duration of the continuous pulsed arc-discharge exposure of these two houseflies.…”
Section: Arcing To Kill Housefliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our supplementary experiment also indicated that the houseflies that approximately 50% of their body water by dehydration received no arcing due to reduced conductance, i.e., an increase in resistivity in the water-depleted houseflies due to the arc-discharge exposure (Figure S1B). Matsuda et al [24] reported that continuous pulsed arc-discharge exposure to the growing stem tip of the kudzu plant (Pueraria montana) raised the temperature of the exposed region, implying that an increase in temperature caused the vaporization of body water. Additionally, we simultaneously transferred two houseflies onto the G-MN and examined the duration of the continuous pulsed arc-discharge exposure of these two houseflies.…”
Section: Arcing To Kill Housefliesmentioning
confidence: 99%
“…The intensity of the arcing is determined by the voltage applied to the conductor and the distance between the opposite poles (charged and grounded conductors); larger voltages and shorter distances generate stronger arcing [21]. The stronger arcing can kill insect pests [17][18][19][20] and weeds [20,24] more effectively and in a shorter time after they enter the electric field. The insects that enter this electric field are exposed to an instantaneous exposure of high-voltage arc discharge from the charged conductor linked to the voltage generator [23].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of unintentional human contact with electric fences, it resulted in only temporary discomfort [46]. For safe usage, the pulse-charging type of voltage generator was employed to operate screens for eliminating invasive kudzu vines climbing on a fence [47], weed seedlings emerging in crop fields [48], and adult houseflies emerging from underground pupae [49]. Recently, Matsuda et al [50] integrated a continuous-charging type of voltage generator into an unattended electric weeder and effectively controlled ground weeds in a greenhouse orchard while ensuring safety.…”
Section: Arc Discharge-generating Electric Field Screen For Eliminati...mentioning
confidence: 99%
“…montana var, lobata [Willd.] Ohwi) creeping along an animal-repelling electric fence [37] and for weed populations growing in crop fields [35]. These approaches suggest that a simple electric weed eradicator could be fabricated easily and inexpensively.…”
Section: Introductionmentioning
confidence: 99%